PENGARUH HARGA, PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PASIEN MELAKUKAN TINDAKAN MEDIS DI ORTHOPEDI CENTRE RS EKA BSD TANGERANG - Kosim Sutiono; Fathorrahman .; Theresia Pradiani (Jurnal Ekonomi Manajemen dan Bisnis, 2023)
The research was carried out by means of a library study, filling out questionnaires with purposive sampling technique methods. In this study, it was determined that the population of patients who underwent medical procedures at the Orthopedic Center of EKA BSD TANGERANG Hospital was 696 patients, through the Slovin formula, a sample of 87 patients was obtained as respondents. The research data was then processed by quantitative methods with Multiple Linear Regression Analysis using SPSS 25. The results showed that each of the variables studied, namely Price, Promotion and Service Quality, each had a significant effect on the patient's decision to take medical action at EKA Hospital BSD Tangerang.